Effect of direct and indirect financial compensation on job satisfaction - Burhanudin, Burhanudin; Tambun, Richard (International research journal of management, IT and social sciences, 2021)
This study aims to examine the effect of direct financial compensation on job satisfaction and to examine the effect of indirect financial compensation on job satisfaction. This type of research is quantitative research. Respondents in this study were 100 employees at PT. Indonesia Asahan Aluminum (Persero), Indonesia. The data collection technique used a questionnaire, while the data analysis technique used multiple linear regression analysis. This study aims to examine the effect of direct financial compensation on job satisfaction and examine the effect of indirect financial compensation on job satisfaction. Based on the results of this study, the company should make an appropriate financial compensation policy, both direct and indirect financial compensation to build employee job satisfaction.